Measuring Receptive Vocabulary Knowledge of Young Learners of English - Kavanoz, Suzan; Varol, Burcu (UNIV GRANADA, 2019)
Vocabulary knowledge that constitutes the milestones of written and roal language is one of the essentials of foreign language learning. Despite its vital importance. vocabulary learning and teaching does not get the necessary attention in L2 learning. As possession of lexical knowledge is a sine qua non for communicative competence, it is essential to study learners' vocabulary levels in Turkey, where English is taught as a foreign language (EFL). Within this context, this study aims to examine the effect of grade level and gender variation in EFL receptive vocabulary size of a group of young learners. The New Vocabulary Levels Test (McLean & Kramer, 2015) was used to determine the receptive vocabulary sizes of young learners across four years of middle school. It was found that all the participating learners know the most frequent 2,000 words in English, which is a critical learning objective for low-level EFL learners. In addition, a developmental pattern, which shows incremental increase in vocabulary size as the grade levels increase, was observed. The findings obtained from this study add to our knowledge of the incremental pattern, of vocabulary development, and of gender differences in vocabulary knowledge.
Keywords: Receptive vocabulary; English as a foreign language; gender differences; grade levels; young learners; SIZE; DEPTH; FREQUENCY; BREADTH; Education & Educational Research; Linguistics